Diastereoselective synthesis of 1,1,4-trisubstituted-2,3,4,9-tetrahydrospiro-beta-carbolines via glacial acetic acid catalyzed pictet - spengler reaction - Shumaila, Abdullah M. A.; Puranik, Vedavati G.; Kusurkar, Radhika S. (Arkivoc, 2011)
The Pictet-Spengler reaction of substituted tryptamines with cyclic ketones using glacial acetic acid afforded only one diastereomer of unreported 1,1,4-trisubstituted-2,3,4,9-tetrahydrospiro-beta-carbolines. The stereoselectivity in the reaction has been demonstrated using unsymmetrical ketones and single-crystal X-ray analysis of one of the spiro products in the form of base, its sulfate and hydrochloride salts, which indicated the formation of only the R, R diastereomer.
Keywords: 1; 3; 4; 4-Trisubstituted-2; 9-tetrahydrospiro-beta-carbolines; beta-substituted tryptamine; Diastereoselective Pictet-Spengler reaction; Glacial acetic acid

Diastereoselective synthesis of tetrasubstituted-octahydro-3,6-diazacarbazoles and tetrasubstituted-3,6-diazacarbazoles via double Pictet-Spengler reaction - Shumaila, Abdullah M. A.; Puranik, Vedavati G.; Kusurkar, Radhika S. (Tetrahedron Letters, 2011)
Pictet-Spengler condensation of 2,5-bis(2-phenyl-1-aminoethyl)pyrrole using glacial acetic acid afforded only one diastereomer of unreported tetrasubstituted-octahydro-3,6-diazacarbazoles. These were readily dehydrogenated to tetrasubstituted-3,6-diazacarbazoles. The stereoselectivity in the Pictet-Spengler reaction has been demonstrated using single crystal X-ray analysis. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: 2; 5-Bis(2-phenyl-1-aminoethyl)pyrrole; 6-diazacarbazoles; Diasteroselective Pictet-Spengler reaction; Glacial acetic acid; Tetrasubstituted-3; Tetrasubstituted-octahydro-3

Synthesis of tetrahydro-5-azaindoles and 5-azaindoles using pictet-spengler reaction-appreciable difference in products using different acid catalysts - Shumaila, Abdullah M. A.; Puranik, Vedavati G.; Kusurkar, Radhika S. (Tetrahedron, 2011)
Pictet-Spengler condensation of 2-(aryl)-2-(1H-pyrrol-2-yl)ethanamines using conventional acid catalysts like TMSCl or TFA resulted in the formation of substituted 5-azaindoles involving a tandem one pot four steps reaction sequence. By contrast use of glacial acetic acid furnished the targeted tetrahydro-5-azaindoles in diastereoselective manner. These were readily dehydrogenated to 5-azaindoles. (C) 2010 Elsevier Ltd. All rights reserved.
Keywords: 2-(Aryl)-2-(1H-pyrrol-2-yl)ethanamines; 4; 7-Disubstituted-5-azaindoles; 7-Disubstituted-tetrahydro-5-azaindoles; Diastereoselective Pictet-Spengler reaction